Only time will tell: A theory of deferred compensation - Florian Hoffmann; Roman Inderst; Marcus M. Opp (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2018)
This paper provides a complete characterization of optimal contracts in principal-agent settings where the agent's action has persistent effects. We model general information environments via the stochastic process of the likelihood-ratio. The martingale property of this performance metric captures the information benefit of deferral. Costs of deferral may result from both the agent's relative impatience as well as her consumption smoothing needs. If the relatively impatient agent is risk neutral, optimal contracts take a simple form in that they only reward maximal performance for at most two payout dates. If the agent is additionally risk-averse, optimal contracts stipulate rewards for a larger selection of dates and performance states: The performance hurdle to obtain the same level of compensation is increasing over time whereas the pay-performance sensitivity is declining.
urn:nbn:de:hebis:30:3-472016
Keywords: D86; 330; compensation design; duration of pay; moral hazard; persistence; principal-agent models; informativeness principle